2015
DOI: 10.1021/acs.jmedchem.5b01008
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Selective Small Molecule Inhibitors of Monoacylglycerol Acyltransferase 3

Abstract: Inhibition of triacylglycerol (TAG) biosynthetic enzymes has been suggested as a promising strategy to treat insulin resistance, diabetes, dyslipidemia, and hepatic steatosis. Monoacylglycerol acyltransferase 3 (MGAT3) is an integral membrane enzyme that catalyzes the acylation of both monoacylglycerol (MAG) and diacylglycerol (DAG) to generate DAG and TAG, respectively. Herein, we report the discovery and characterization of the first selective small molecule inhibitors of MGAT3. Isoindoline-5-sulfonamide (6f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 37 publications
1
10
0
Order By: Relevance
“…The relative contributions of MGAT2 and MGAT3 to hepatic lipid metabolism are unknown. To probe the role that each enzyme has in TG synthesis and secretion in HepG2 cells we utilized the highly selective MGAT2 and MGAT3 small molecule inhibitors, Cpd24d and PF-06471553, respectively, to attenuate MGAT activity 34 , 35 . We first confirmed that these compounds effectively inhibited MGAT activity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The relative contributions of MGAT2 and MGAT3 to hepatic lipid metabolism are unknown. To probe the role that each enzyme has in TG synthesis and secretion in HepG2 cells we utilized the highly selective MGAT2 and MGAT3 small molecule inhibitors, Cpd24d and PF-06471553, respectively, to attenuate MGAT activity 34 , 35 . We first confirmed that these compounds effectively inhibited MGAT activity.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, we tested the hypothesis that MGAT2 and/or MGAT3 can contribute to TG synthesis and secretion in the liver via the MGAT pathway. To test this, we inhibited MGAT2 and MGAT3 in HepG2 cells with highly selective small-molecule inhibitors and examined the effects on lipid metabolism 34 , 35 . We found that MGAT2, much more so than MGAT3, contributed to hepatic TG synthesis and secretion.…”
Section: Introductionmentioning
confidence: 99%
“…Glucose was chosen for the simultaneous labeling of acyl chains and glycerol based on a recent plant-based study that demonstrated a lack of incorporation of label into fatty acids using glycerol itself (40). The incorporation of stable isotopically labeled glycerol into the TG pool as a proxy for the activity of complex lipid remodeling enzymes is an established technique (41).…”
Section: Resultsmentioning
confidence: 99%
“…It is unknown whether targeting MGAT3 will be effective in treating humans. MGAT3 specific inhibitors have been designed and preliminary studies in transgenic mice expressing MGAT3 have demonstrated efficacy in vivo , though further phenotypic characterization has not been reported (Huard et al, 2015).…”
Section: Peroxisome Proliferator-activated Receptor Agonists (Ppar’s)mentioning
confidence: 99%